Alat Ambulatory Blood Pressure Monitor dan Pengukur Suhu Via Aplikasi Android - Ariman Ariman (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
ABSTRACT Hypertension is one of the serious diseases that are many people are facing these days, the absence of regular checks makes a person not aware of the state of blood pressure in his body. The solution is by having a blood pressure, pulse and body temperature measuring device that can monitor blood pressure, pulse and body temperature continuously for ± 24 hours. This tool system uses the MPX5700 pressure sensor to detect blood pressure and pulse, as a body temperature detector using a DS18B20 temperature sensor and using the Arduino microcontroller as a data processor. The measurement is made by attaching the cuff in patient arm, then pumped automatically with a certain pressure, then the measurement of blood pressure, pulse and body temperature were carried out, the results are displayed on the android device and can be printed through the printer. Keywords: hypertension; blood pressure; temperature; monitor; tool.